GenAI in SMEs : Navigating Implementation Challenges in Selected European Contexts - Santoro, Lorenzo (2024)
This thesis concentrates on the barriers and challenges small and medium enterprises (SMEs) in the Italian Market face in implementing Generative AI (GenAI) tools. It explores different obstacles (technical, operational, and financial among others) that these businesses encounter, highlighting different approaches to GenAI adoption in SMEs.